2000
DOI: 10.1021/ie990871l
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of CO and COS Formation in the Claus Furnace

Abstract: The aim of this study was to determine the major pathways leading to COS and CO formation and consumption during the processing of H2S and CO2 in the partially oxidizing conditions of the Claus furnace. Both species were found to be produced by a multitude of pathways, which include the direct reaction of H2S with CO2 to form COS and H2O and the reaction of CO2 with S2, one of the major primary products in a Claus furnace. This last reaction produced SO2 and CO as the major products, with COS being formed in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 20 publications
5
63
0
Order By: Relevance
“…Experimental results for oxidation of CS 2 These data sets were obtained in an overlapping temperature and pressure range but under conditions of low (300 ppm 7 ) and high (25% 8,14 ) concentrations of CS 2 , respectively. Figure 6 compares the measured and calculated explosion limits.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental results for oxidation of CS 2 These data sets were obtained in an overlapping temperature and pressure range but under conditions of low (300 ppm 7 ) and high (25% 8,14 ) concentrations of CS 2 , respectively. Figure 6 compares the measured and calculated explosion limits.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the experiments, the reactants CS 2 and O 2 were preheated separately and mixed at the entrance to the reaction zone. Atomic oxygen, formed from O 2 at the heating elements in the preheating oven, was suggested to promote onset of reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of carbon and oxygen in the chalcopyrite, and formation of CS 2 and CO 2 in the gas phase during leaching, is reminiscent of a Stock-like reaction mechanism (4). 44,45 …”
Section: Article This Journal Is © the Royal Society Of Chemistry 20xxmentioning
confidence: 99%
“…Paskal et al gives a summary of the main reactions thought to occur within the Claus furnace [6,7]. Clark et al discussed the mechanisms behind the formation of key sulfur containing species found within the furnace, and in a subsequent study outline primary reaction pathways for the principal components in the furnace [8,9]. While there have been numerous attempts to model the Claus process based on simplified kinetic expressions, the complexity of the chemistry and the number of involved reactions has precluded the accurate prediction of outlet compositions.…”
Section: Kinetic Studiesmentioning
confidence: 99%